Small Cell Carcinoma of the Ovary (Hypercalcemic Type): Malignant Rhabdoid Tumor - Kascak, Peter; Zamecnik, Michal; Bystricky, Branislav (Case reports in oncology, 2016)
We present a rare case of malignant rhabdoid tumor (ovarian small cell carcinoma of hypercalcemic type) in a 24-year-old female with fulminant course. Clinically, hypercalcemia was not found at the time of primary diagnosis. However, it appeared later during the course of tumor progression. Histologically, the tumor showed classical features of small cell carcinoma of hypercalcemic type. Therapy included radical surgery with adjuvant chemotherapy. Despite this intensive therapy, the disease recurred and the patient died 10 months after the diagnosis. We discuss the diagnosis and therapy of this tumor, as well as its recent classification as malignant rhabdoid tumor.